O serviço à comunhão em Tillard: os Ministérios - Kunrath, Pedro Alberto (Teocomunicação, 2006)
Christian communities are sure that they receive the gifts from the Holy Ghost, for the advantage of all the members. When a man or a woman helps the community, they exercise a ministry and such an attitude belongs to the essence of the Church.